A potential new sea surface temperature proxy based on isomeric highly branched isoprenoid lipid biomarkers: EZ25 - Belt, Simon T.; Smik, Lukas; Husum, Katrine; Knies, Jochen (Organic Geochemistry, 2025)
Two tri-unsaturated and isomeric (E/Z) highly branched isoprenoid (HBI) diatom lipid biomarkers were quantified in 228 water column samples collected from the English Channel, West Svalbard (Arctic), the Scotia Sea (Southern Ocean) and East Antarctica. We found that the relative amounts of the two HBIs correlate well with water temperatures taken at the time of sampling. Based on these findings and some other HBI data reported previously, we suggest that the proportion of the HBI E-isomer (termed EZ25) may serve as a new proxy for palaeo sea surface temperatures, including in the polar regions. Next steps will involve determination of EZ25 in surface and downcore sediments to ascertain whether the temperature response described herein translates well to the geological record.
Article number: 105056
Keywords: Scotiahavet; Sørishavet; biogeokjemi; biomarkører; geologi; paleontologi; polarområdene

Observation-Based Estimate of Net Community Production in Antarctic Sea Ice - Dalman, Laura A.; Meiners, Klaus M.; Thomas, David N.; Deman, Florian; Bestley, Sophie; Moreau, Sébastien; Arrigo, Kevin R.; Campbell, Karley; Corkill, Matthew; Cozzi, Stefano; Delille, Bruno; Fransson, Agneta; et al. (Geophysical Research Letters, 2025)
Abstract Antarctic sea ice is one of the largest biomes on Earth providing a critical habitat for ice algae. Measurements of primary production in Antarctic sea ice remain scarce and an observation-based estimate of primary production has not been revisited in over 30 years. We fill this knowledge gap by presenting a newly compiled circumpolar data set of particulate and dissolved organic carbon from 362 ice cores, sampled between 1989 and 2019, to estimate sea-ice net community production using a carbon biomass accumulation approach. Our estimate of 26.8?32.9 Tg C yr?1 accounts for at least 15%?18% of the total primary production in the Antarctic sea-ice zone, less than a previous observation-based estimate (63?70 Tg C yr?1) and consistent with recent modeled estimates. The results underpin the ecological significance of sea-ice algae as an early season resource for pelagic food webs.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; biogeokjemi; fotosyntese; havis alger; karbondioksid; karbonsyklus; oseanografi; primærproduksjon; sjøis

A chlorophyll halo over maud rise in the southern ocean - Ducrocq, Bertrand; Steiger, Nadine; du Plessis, Marcel; Sallée, Jean-Baptiste; Moreau, Sébastien; Swart, Sebastiaan (Nature communications, 2025)
Phytoplankton blooms above the seamount Maud Rise in the Antarctic Ocean have been reported but their emerging mechanisms and their importance for the wider Southern Ocean are not well known. We use satellite data spanning over the last two decades and in-situ data collected from a ship, an underwater glider and Biogeochemical-Argo profiling floats to understand the processes involved in the formation of Maud Rise phytoplankton blooms. We find that the seamount generates upwelling of warm deep water that transports heat, and likely dissolved iron, to the surface via diapycnal mixing. This creates a recurring annular structure of chlorophyll concentration (or chlorophyll halo) in correspondence with the previously observed warm water and sea ice halo over Maud Rise. The in-situ observations reveal integrated chlorophyll-a concentrations of up to 100 mg·m(-2), which suggests exceptionally high phytoplankton biomass within the Southern Ocean, thus making the seamount a regional phytoplankton hotspot.
Place: England
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; marin biologi; oseanografi

Southern Ocean Carbon Export Revealed by Backscatter and Oxygen Measurements From BGC-Argo Floats - Liniger, Guillaume; Moreau, Sébastien; Lannuzel, Delphine; Carranza, Magdalena M.; Strutton, Peter G. (Global Biogeochemical Cycles, 2025)
The Southern Ocean (south of 30°S) contributes significantly to global ocean carbon uptake through the solubility, physical and biological pumps. Many studies have estimated carbon export to the deep ocean, but very few have attempted a basin-scale perspective, or accounted for the sea-ice zone (SIZ). In this study, we use an extensive array of BGC-Argo floats to improve previous estimates of carbon export across basins and frontal zones, specifically including the SIZ. Using a new method involving changes in particulate organic carbon and dissolved oxygen along the mesopelagic layer, we find that the total Southern Ocean carbon export from 2014 to 2022 is 2.69 ± 1.23 PgC y?1. The polar Antarctic zone contributes the most (41%) with 1.09 ± 0.46 PgC y?1. Conversely, the SIZ contributes the least (8%) with 0.21 ± 0.09 PgC y?1 and displays a strong shallow respiration in the upper 200 m. However, the SIZ contribution can increase up to 14% depending on the depth range investigated. We also consider vertical turbulent fluxes, which can be neglected at depth but are important near the surface. Our work provides a complementary approach to previous studies and is relevant for work that focuses on evaluating the biogeochemical impacts of changes in Antarctic sea-ice extent. Refining estimates of carbon export and understanding its drivers ultimately impacts our comprehension of climate variability at the global ocean scale.
Publisher: John Wiley & Sons, Ltd Article number: e2024GB008193
Keywords: Sørishavet; biogeokjemi; fotosyntese; fytoplankton; havis; karbon syklus; sjøis

Giant iceberg meltwater increases upper-ocean stratification and vertical mixing - Lucas, Natasha S.; Brearley, J. Alexander; Hendry, Katharine R.; Spira, Theo; Braakmann-Folgmann, Anne; Abrahamsen, E. Povl; Meredith, Michael P.; Tarling, Geraint A. (Nature Geoscience, 2025)
Ice-sheet mass loss is one of the clearest manifestations of climate change, with Antarctica discharging mass into the ocean via melting or through calving. The latter produces icebergs that can modify ocean water properties, often at great distances from source. This affects upper-ocean physics and primary productivity, with implications for atmospheric carbon drawdown. A detailed understanding of iceberg modification of ocean waters has hitherto been hindered by a lack of proximal measurements. Here unique measurements of a giant iceberg from an underwater glider enable quantification of meltwater effects on the physical and biological processes in the upper layers of the Southern Ocean, a region disproportionately important for global heat and carbon sequestration. Iceberg basal melting erodes seasonally produced winter water layer stratification, normally forming a strong potential energy barrier to vertical exchange of surface and deep waters, while freshwater run-off increases and shoals near-surface stratification. Nutrient-rich deeper waters, incorporating meltwater loaded with terrigenous material, are ventilated to below this stratification maxima, providing a potential mechanism for alleviating critical phytoplankton-limiting components. Regional historical hydrographic data demonstrate similar stratification changes during the passage of another large iceberg, suggesting that they may be an important pathway of aseasonal winter water modification.
Keywords: Sørishavet; Weddellhavet; biogeokjemi; glasiologi; global oppvarming; hydrografi; klimaendringer; klimatologi; oseanografi

Phytoplankton bloom distribution and succession driven by sea-ice melt in the Kong Håkon VII Hav - Lenss, Megan; Moreau, Sebastien; Hattermann, Tore; Wiktor, Jozef; Różańska, Magdalena; Claeys, Philippe; Brion, Natacha; Chierici, Melissa; Fransson, Agneta; Campbell, Karley (Elementa: Science of the Anthropocene, 2024)
The existence of ice-edge phytoplankton blooms in the Southern Ocean is well described, yet direct observations of the mechanisms of phytoplankton bloom development following seasonal sea-ice melt remain scarce. This study constrains such responses using biological and biogeochemical datasets collected along a coastal-to-offshore transect that bisects the receding sea-ice zone in the Kong Håkon VII Hav (off the coast of Dronning Maud Land). We documented that the biogeochemical growing conditions for phytoplankton vary on a latitudinal gradient of sea-ice concentration, where increased sea-ice melting creates optimal conditions for growth with increased light availability and potentially increased iron supply. The zones of the study area with the least ice cover were associated with diatom dominance, the greatest chlorophyll a concentrations, net community production, and dissolved inorganic carbon drawdown, as well as lower sea surface fugacity of CO2. Together, these associations imply higher potential for an oceanic CO2 sink due, at least in part, to more advanced bloom phase and/or larger bloom magnitude stemming from a relatively longer period of light exposure, as compared to the more ice-covered zones in the study area. From stable oxygen isotope fractions, sea-ice meltwater fractions were highest in the open ocean zone and meteoric meltwater fractions were highest in the coastal and polynya zones, suggesting that potential iron sources may also change on a latitudinal gradient across the study area. Variable phytoplankton community compositions were related to changing sea-ice concentrations, with a typical species succession from sympagic flagellate species (Pyramimonas sp. and Phaeocystis antarctica) to pelagic diatoms (e.g., Dactyliosolen tenuijunctus) observed across the study area. These results fill a spatiotemporal gap in the Southern Ocean, as sea-ice melting plays a larger role in governing phytoplankton bloom dynamics in the future Southern Ocean due to changing sea-ice conditions caused by anthropogenic global warming.
Article Number: 00122
Keywords: Sørishavet; biogeokjemi; fytoplankton; havis; oseanografi; sjøis

Antarctic Blue Ice Areas are hydrologically active, nutrient rich and contain microbially diverse cryoconite holes - Nowak, Aga; Isaksson, Elisabeth; Sunde, Øyvind; Elvevold, Synnøve; Sandven, Håkon; Moholdt, Geir; Hudson, Stephen R.; Urset, Anne; Edwards, Arwyn; Rassner, Sara M. E.; Pearce, David; Hamre, Børge; et al. (Communications Earth & Environment, 2024)
Antarctica is the coldest, windiest and least inhabited place on Earth. One of its most enigmatic regions is scoured by katabatic winds blue ice that covers 235,000 km2 of the Antarctic fringe. Here, we demonstrate that contrary to common belief, high-altitude inland blue ice areas are not dry, nor barren. Instead, they promote sub-surface melting that enables them to become “powerplants” for water, nutrients, carbon and major ions production. Mapping cryoconite holes at an unprecedented scale of 62 km2 also revealed a regionally significant resource of dissolved nitrogen, phosphorus (420 kg km−2), dissolved carbon (1323 kg km−2), and major ions (6672 kg km−2). We discovered that unlike on glaciers, creation of cryoconite holes and their chemical signature on the ice sheet is governed by ice movement and bedrock geology. Blue ice areas are near-surface hotspots of microbial life within cryoconite holes. Bacterial communities they support are unexpectedly diverse. We also show that near-surface aquifers can exist in blue ice outside cryoconite holes. Identifying blue ice areas as active ice sheet ecosystems will help us understand the role ice sheets play in Antarctic carbon cycle, development of near-surface drainage system, and will expand our perception of the limits of life.
Keywords: Antarktis; biogeokjemi; geografi; geologi; mikrobielle organismer; mikrobiologi

Gross Primary Production of Antarctic Landfast Sea Ice: A Model-Based Estimate - Wongpan, Pat; Meiners, K. M.; Vancoppenolle, M.; Fraser, A. D.; Moreau, Sebastien; Saenz, B. T.; Swadling, K. M.; Lannuzel, D. (Journal of Geophysical Research: Oceans, 2024)
Much of the Antarctic coast is covered by seasonal landfast sea ice (fast ice), which serves as an important habitat for ice algae. Fast-ice algae provide a key early season food source for pelagic and benthic food webs, and contribute to biogeochemical cycling in Antarctic coastal ecosystems. Summertime fast ice is undergoing a decline, leading to more seasonal fast ice with unknown impacts on interconnected Earth system processes. Our understanding of the spatiotemporal variability of Antarctic fast ice, and its impact on polar ecosystems is currently limited. Evaluating the overall productivity of fast-ice algae has historically been hampered by limitations in observations and models. By linking new fast-ice extent maps with a one-dimensional sea-ice biogeochemical model, we provide the first estimate of the spatio-seasonal variability of Antarctic fast-ice algal gross primary production (GPP) and its annual primary production on a circum-Antarctic scale. Experiments conducted for the 2005?2006 season provide a mean fast ice-algal production estimate of 2.8 Tg C/y. This estimate represents about 12% of overall Southern Ocean sea-ice algae production (estimated in a previous study), with the mean fast-ice algal production per area being 3.3 times higher than that of pack ice. Our Antarctic fast-ice GPP estimates are probably underestimated in the Ross Sea and Weddell Sea sectors because the sub-ice platelet layer habitats and their high biomass are not considered.
Publisher: John Wiley & Sons, Ltd Article Number: e2024JC021348
Keywords: Sørishavet; alger; biogeokjemi; geofysikk; havis; oseanografi; sjøis

Physical and Biogeochemical Properties of Rotten East Antarctic Summer Sea Ice - Corkill, M.; Moreau, S.; Janssens, J.; Fraser, A. D.; Heil, P.; Tison, J.-L.; Cougnon, E. A.; Genovese, C.; Kimura, N.; Meiners, K. M.; Wongpan, P.; Lannuzel, D. (Journal of Geophysical Research: Oceans, 2023)
Sea ice forms a barrier to the exchange of energy, gases, moisture and particles between the ocean and atmosphere around Antarctica. Ice temperature, salinity and the composition of ice crystals determine whether a particular slab of sea ice is habitable for microorganisms and permeable to exchanges between the ocean and atmosphere, allowing, for example, carbon dioxide (CO2) from the atmosphere to be absorbed or outgassed by the ocean. Spring sea ice can have high concentrations of algae and absorb atmospheric CO2. In the summer of 2016?2017 off East Antarctica, we found decayed and porous granular ice layers in the interior of the ice column, which showed high algal pigment concentrations. The maximum chlorophyll a observed in the interior of the ice column was 67.7 ?g/L in a 24% porous granular ice layer between 0.8 and 0.9 m depth in 1.7 m thick ice, compared to an overall mean sea-ice chlorophyll a (± one standard deviation) of 13.5 ± 21.8 ?g/L. We also found extensive surface melting, with instances of snow meltwater apparently percolating through the ice, as well as impermeable superimposed ice layers that had refrozen along with melt ponds on top of the ice. With future warming, the structures we describe here could occur earlier and/or become more persistent, meaning that sea ice would be more often characterized by patchy permeability and interior ice algal accumulations.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; biogeokjemi; havis; isfjell

A review of the scientific knowledge of the seascape off Dronning Maud Land, Antarctica - Lowther, Andrew; von Quillfeldt, Cecilie; Assmy, Philipp; De Steur, Laura; Descamps, Sebastien; Divine, Dmitry; Elvevold, Synnøve; Forwick, Matthias; Fransson, Agneta; Fraser, Alexander; Gerland, Sebastian; Granskog, Mats; et al. (Polar Biology, 2022)
Despite the exclusion of the Southern Ocean from assessments of progress towards achieving the Convention on Biological Diversity (CBD) Strategic Plan, the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) has taken on the mantle of progressing efforts to achieve it. Within the CBD, Aichi Target 11 represents an agreed commitment to protect 10% of the global coastal and marine environment. Adopting an ethos of presenting the best available scientific evidence to support policy makers, CCAMLR has progressed this by designating two Marine Protected Areas in the Southern Ocean, with three others under consideration. The region of Antarctica known as Dronning Maud Land (DML; 20°W to 40°E) and the Atlantic sector of the Southern Ocean that abuts it conveniently spans one region under consideration for spatial protection. To facilitate both an open and transparent process to provide the vest available scientific evidence for policy makers to formulate management options, we review the body of physical, geochemical and biological knowledge of the marine environment of this region. The level of scientific knowledge throughout the seascape abutting DML is polarized, with a clear lack of data in its eastern part which is presumably related to differing levels of research effort dedicated by national Antarctic programmes in the region. The lack of basic data on fundamental aspects of the physical, geological and biological nature of eastern DML make predictions of future trends difficult to impossible, with implications for the provision of management advice including spatial management. Finally, by highlighting key knowledge gaps across the scientific disciplines our review also serves to provide guidance to future research across this important region.
Keywords: Dronning Maud Land; Sørishavet; biofysikk; biogeokjemi; biologi; oseanografi

Evidence for the Impact of Climate Change on Primary Producers in the Southern Ocean - Pinkerton, Matthew H; Boyd, Philip W; Deppeler, Stacy; Hayward, Alex; Höfer, Juan; Moreau, Sebastien (Frontiers in Ecology and Evolution, 2021)
Within the framework of the Marine Ecosystem Assessment for the Southern Ocean (MEASO), this paper brings together analyses of recent trends in phytoplankton biomass, primary production and irradiance at the base of the mixed layer in the Southern Ocean and summarises future projections. Satellite observations suggest that phytoplankton biomass in the mixed-layer has increased over the last 20 years in most (but not all) parts of the Southern Ocean, whereas primary production at the base of the mixed-layer has likely decreased over the same period. Different satellite models of primary production (Vertically Generalised versus Carbon Based Production Models) give different patterns and directions of recent change in net primary production (NPP). At present, the satellite record is not long enough to distinguish between trends and climate-related cycles in primary production. Over the next 100 years, Earth system models project increasing NPP in the water column in the MEASO northern and Antarctic zones but decreases in the Subantarctic zone. Low confidence in these projections arises from: (1) the difficulty in mapping supply mechanisms for key nutrients (silicate, iron); and (2) understanding the effects of multiple stressors (including irradiance, nutrients, temperature, pCO_2, pH, grazing) on different species of Antarctic phytoplankton. Notwithstanding these uncertainties, there are likely to be changes to the seasonal patterns of production and the microbial community present over the next 50–100 years and these changes will have ecological consequences across Southern Ocean food-webs, especially on key species such as Antarctic krill and silverfish.
Keywords: Sørishavet; biogeokjemi; fytoplankton; klimaendringer; marine økosystemer; phytoplankton

Meridional Ocean Carbon Transport - Aldama-Campino, Aitor; Fransner, Filippa; Ödalen, Malin; Groeskamp, Sjoerd; Yool, Andrew; Döös, Kristofer; Nycander, Jonas (Global Biogeochemical Cycles, 2020)
The ocean's ability to take up and store CO2 is a key factor for understanding past and future climate variability. However, qualitative and quantitative understanding of surface-to-interior pathways, and how the ocean circulation affects the CO2 uptake, is limited. Consequently, how changes in ocean circulation may influence carbon uptake and storage and therefore the future climate remains ambiguous. Here we quantify the roles played by ocean circulation and various water masses in the meridional redistribution of carbon. We do so by calculating streamfunctions defined in dissolved inorganic carbon (DIC) and latitude coordinates, using output from a coupled biogeochemical-physical model. By further separating DIC into components originating from the solubility pump and a residual including the biological pump, air-sea disequilibrium, and anthropogenic CO2, we are able to distinguish the dominant pathways of how carbon enters particular water masses. With this new tool, we show that the largest meridional carbon transport occurs in a pole-to-equator transport in the subtropical gyres in the upper ocean. We are able to show that this pole-to-equator DIC transport and the Atlantic meridional overturning circulation (AMOC)-related DIC transport are mainly driven by the solubility pump. By contrast, the DIC transport associated with deep circulation, including that in Antarctic bottom water and Pacific deep water, is mostly driven by the biological pump. As these two pumps, as well as ocean circulation, are widely expected to be impacted by anthropogenic changes, these findings have implications for the future role of the ocean as a climate-buffering carbon reservoir.
Keywords: Sørishavet; biogeokjemi; bunnvann; karbon syklus; karbondioksid; klimatologi; oseanografi; vannmasser

Two-Timescale Carbon Cycle Response to an AMOC Collapse - Nielsen, Søren B; Jochum, Markus; Pedro, Joel B; Eden, Carsten; Nuterman, Roman (Paleoceanography and Paleoclimatology, 2019)
Atmospheric CO2 concentrations (pCO2) varied on millennial timescales in phase with Antarctic temperature during the last glacial period. A prevailing view has been that carbon release and uptake by the Southern Ocean dominated this millennial-scale variability in pCO2. Here, using Earth System Model experiments with an improved parameterization of ocean vertical mixing, we find a major role for terrestrial and oceanic carbon releases in driving the pCO2 trend. In our simulations, a change in Northern Hemisphere insolation weakens the Atlantic Meridional Overturning Circulation (AMOC) leading to increasing pCO2 and Antarctic temperatures. The simulated rise in pCO2 is caused in equal parts by increased CO2 outgassing from the global ocean due to a reduced biological activity and changed ventilation rates, and terrestrial carbon release as a response to southward migration of the Intertropical Convergence Zone. The simulated terrestrial release of carbon could explain stadial declines in organic carbon reservoirs observed in recent ice core δ13C measurements. Our results show that parallel variations in Antarctic temperature and pCO2 do not necessitate that the Southern Ocean dominates carbon exchange; instead, changes in carbon flux from the global ocean and land carbon reservoirs can explain the observed pCO2 (and δ13C) changes.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; klimatologi; paleoklimatologi; paleoseanografi; temperatur

Net Community Production in the Southern Ocean: Insights From Comparing Atmospheric Potential Oxygen to Satellite Ocean Color Algorithms and Ocean Models - Nevison, Cynthia; Munro, David; Lovenduski, Nicole; Cassar, Nicolas; Keeling, Ralph; Krummel, Paul; Tjiputra, Jerry (Geophysical Research Letters, 2018)
The contribution of oceanic net community production (NCP) to the observed seasonal cycle in atmospheric potential oxygen (APO) is estimated at Cape Grim, Tasmania. The resulting APONCP signal is compared to satellite and ocean model-based estimates of POC export and NCP across the Southern Ocean. The satellite products underestimate the amplitude of the observed APONCP seasonal cycle by more than a factor of 2. Ocean models suggest two reasons for this underestimate: (1) Current satellite products substantially underestimate the magnitude of NCP in early spring. (2) Seasonal O2 outgassing is supported in large part by storage of carbon in DOC and living biomass. More DOC observations are needed to help evaluate this latter model prediction. Satellite products could be improved by developing seasonally dependent relationships between remote sensing chlorophyll data and in situ NCP, recognizing that the former is a measure of mass, the latter of flux.
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; karboneksport; marin biologi; oseanografi

Remarkable structural resistance of a nanoflagellate-dominated plankton community to iron fertilization during the Southern Ocean experiment LOHAFEX - Schulz, Isabelle; Montresor, Marina; Klaas, Christine; Assmy, Philipp; Wolzenburg, Sina; Gauns, Mangesh; Sarkar, Amit; Thiele, Stefan; Wolf-Gladrow, Dieter; Naqvi, Wajih; Smetacek, Victor (Marine Ecology Progress Series, 2018)
The genesis of phytoplankton blooms and the fate of their biomass in iron-limited, high-nutrient-low-chlorophyll regions can be studied under natural conditions with ocean iron fertilization (OIF) experiments. The Indo-German OIF experiment LOHAFEX was carried out over 40 d in late summer 2009 within the cold core of a mesoscale eddy in the productive south-west Atlantic sector of the Southern Ocean. Silicate concentrations were very low, and phytoplankton biomass was dominated by autotrophic nanoflagellates (ANF) in the size range 3-10 µm. As in all previous OIF experiments, the phytoplankton responded to iron fertilization by increasing the maximum quantum yield (Fv/Fm) and cellular chlorophyll levels. Within 3 wk, chlorophyll levels tripled and ANF biomass doubled. With the exception of some diatoms and dinoflagellates, the biomass levels of all other groups of the phyto- and protozooplankton (heterotrophic nanoflagellates, dinoflagellates and ciliates) remained remarkably stable throughout the experiment both inside and outside the fertilized patch. We attribute the unusually high biomass attained and maintained by ANF to the absence of their grazers, the salps, and to constraints on protozooplankton grazers by heavy predation exerted by the large copepod stock. The resistance to change of the ecosystem structure over 38 d after fertilization, indicated by homogeneity at regional and temporal scales, suggests that it was locked into a stable, mature state that had evolved in the course of the seasonal cycle. The LOHAFEX bloom provides a case study of a resistant/robust dynamic equilibrium between auto- and heterotrophic ecosystem components resulting in low vertical flux both inside and outside the patch despite high biomass levels. KEYWORDS: Antarctic · Protists · Fe-limitation · Si-limitation · Ecology-biogeochemistry relationship · Carbon:chlorophyll ratios · Ecosystem stability
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; marin biologi; økologi; økosystemer

Microbes influence the biogeochemical and optical properties of maritime Antarctic snow - Hodson, Andrew; Nowak, Aga; Cook, Joseph; Sabacka, Marie; Wharfe, Emma S; Pearce, David Anthony; Convey, Peter; Vieira, Gonçalo (Journal of Geophysical Research: Biogeosciences, 2017)
Snowmelt in the Antarctic Peninsula region has increased significantly in recent decades, leading to greater liquid water availability across a more expansive area. As a consequence, changes in the biological activity within wet Antarctic snow require consideration if we are to better understand terrestrial carbon cycling on Earth's coldest continent. This paper therefore examines the relationship between microbial communities and the chemical and physical environment of wet snow habitats on Livingston Island of the maritime Antarctic. In so doing, we reveal a strong reduction in bacterial diversity and autotrophic biomass within a short (<1 km) distance from the coast. Coastal snowpacks, fertilized by greater amounts of nutrients from rock debris and marine fauna, develop obvious, pigmented snow algal communities that control the absorption of visible light to a far greater extent than with the inland glacial snowpacks. Absorption by carotenoid pigments is most influential at the surface, while chlorophyll is most influential beneath it. The coastal snowpacks also indicate higher concentrations of dissolved inorganic carbon and CO2 in interstitial air, as well as a close relationship between chlorophyll and dissolved organic carbon (DOC). As a consequence, the DOC resource available in coastal snow can support a more diverse bacterial community that includes microorganisms from a range of nearby terrestrial and marine habitats. Therefore, since further expansion of the melt zone will influence glacial snowpacks more than coastal ones, care must be taken when considering the types of communities that may be expected to evolve there.
Keywords: Antarktis; biogeokjemi; mikrobiologi; mikroorganismer; snøalger; snøpakke; snøsmelting

Autonomous observing platform CO2 data shed new light on the Southern Ocean carbon cycle - Olsen, Are (Global Biogeochemical Cycles, 2017)
While the number of surface ocean CO2 partial pressure (pCO2) measurements has soared the recent decades, the Southern Ocean remains undersampled. Williams et al. (2017, https://doi.org/10.1002/2016GB005541) now present pCO2 estimates based on data from pH-sensor equipped Bio-Argo floats, which have been measuring in the Southern Ocean since 2014. The authors demonstrate the utility of these data for understanding the carbon cycle in this region, which has a large influence on the distribution of CO2 between the ocean and atmosphere. Biogeochemical sensors deployed on autonomous platforms hold the potential to shape our view of the ocean carbon cycle in the coming decades.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; kartlegging; klimaendringer; klimatologi; observasjoner

Observation-Based Trends of the Southern Ocean Carbon Sink - Ritter, Rebecca; Landschützer, Peter; Gruber, Nicolas; Fay, Amanda R; Iida, Yosuke; Jones, Stephen Daniel; Nakaoka, Shin-ichiro; Park, Geun-Ha; Peylin, Philippe; Rödenbeck, Christian; Rodgers, Keith B; Shutler, Jamie D; et al. (Geophysical Research Letters, 2017)
The Southern Ocean (SO) carbon sink has strengthened substantially since the year 2000, following a decade of a weakening trend. However, the surface ocean pCO2 data underlying this trend reversal are sparse, requiring a substantial amount of extrapolation to map the data. Here we use nine different pCO2 mapping products to investigate the SO trends and their sensitivity to the mapping procedure. We find a robust temporal coherence for the entire SO, with eight of the nine products agreeing on the sign of the decadal trends, that is, a weakening CO2 sink trend in the 1990s (on average 0.22 ± 0.24 Pg C yr−1 decade−1), and a strengthening sink trend during the 2000s (−0.35 ± 0.23 Pg C yr−1 decade−1). Spatially, the multiproduct mean reveals rather uniform trends, but the confidence is limited, given the small number of statistically significant trends from the individual products, particularly during the data-sparse 1990–1999 period.
Keywords: Sørishavet; biogeokjemi; global oppvarming; karbondioksid; klimaendringer; klimatologi; meteorologi

Molluscan assemblages associated with Gigartina beds in the Strait of Magellan and the South Shetland Islands (Antarctica): a comparison of composition and abundance - Rosenfeld, Sebastián; Aldea, Cristian; Ojeda, Jaime; Marambio, Johanna; Hüne, Mathias; Troncoso, Jesús S; Mansilla, Andrés (Polar Research, 2017)
In this paper we evaluated the composition and abundance of molluscs associated with beds of the red algae Gigartina, located in the South Shetland Islands (Antarctic Peninsula) and the Strait of Magellan (southern Chile). During the summer season of 2013, samples were obtained by scuba diving using a 0.25 m2 quadrat, arranged randomly within the bed. We extracted a total of 15 quadrats per sampling site. For Antarctic Peninsula beds the most abundant species were the bivalve Lissarca miliaris (233 individuals) and the gastropod Laevilacunaria antarctica (94 individuals), while for Strait of Magellan beds the most abundant species was the polyplacophoran Callochiton puniceus (36 individuals). Comparative analysis between the two molluscan assemblages showed significant differences in the faunal composition between the Antarctic Peninsula and Strait of Magellan (f = 64.474; p = 0.0001). Therefore, molluscs reported in both areas are characteristic of their respective biogeographic area. Finally, Gigartina species play an important role in the formation of patterns of abundance and diversity of the communities associated with them.
Keywords: Sørishavet; alger; biodiversitet; biogeokjemi; bløtdyr; havbunnen; muslinger; snegler

Evaluating CMIP5 ocean biogeochemistry and Southern Ocean carbon uptake using atmospheric potential oxygen: Present-day performance and future projection - Nevison, Cynthia; Manizza, Manfredi; Keeling, Ralph; Stephens, Britton; Bent, Jonathan; Dunne, John P; Ilyina, Tatiana; Long, Matthew; Resplandy, Laure; Tjiputra, Jerry; Yukimoto, Seiji (Geophysical Research Letters, 2016)
Observed seasonal cycles in atmospheric potential oxygen (APO ~ O2 + 1.1 CO2) were used to evaluate eight ocean biogeochemistry models from the Coupled Model Intercomparison Project (CMIP5). Model APO seasonal cycles were computed from the CMIP5 air-sea O2 and CO2 fluxes and compared to observations at three Southern Hemisphere monitoring sites. Four of the models captured either the observed APO seasonal amplitude or phasing relatively well, while the other four did not. Many models had an unrealistic seasonal phasing or amplitude of the CO2 flux, which in turn influenced APO. By 2100 under RCP8.5, the models projected little change in the O2 component of APO but large changes in the seasonality of the CO2 component associated with ocean acidification. The models with poorer performance on present-day APO tended to project larger net carbon uptake in the Southern Ocean, both today and in 2100.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; klimatologi; meteorologi; oseanografi

The significant inputs of trace elements and rare earth elements from melting glaciers in Antarctic coastal waters - Kim, Intae; Kim, Guebuem; Choy, Eun Jung (Polar Research, 2015)
To evaluate the impact of modern glacier melting on the chemical enrichment of Antarctic coastal waters, we measured trace elements, including dissolved iron (Fe) and rare earth elements (REEs), together with dissolved inorganic nitrogen, phosphorous, silicate and dissolved organic carbon (DOC) in ice, snow and coastal seawater of Marian Cove in the northernmost part of Antarctica (62°S). There was an increase in the concentrations of Fe and other trace elements (Al, Mn, Cr, Ni, Co, Pb and REEs) between the bay mouth and the glacier valleys. Good correlations between salinity and these chemical elements indicate that the trend was mainly due to the influence of glacier meltwater (GMW). When the effect of GMW was quantified based on plots of its presence (average 5.7%) in the surface water of the cove, the concentrations of trace elements in seawater increased 18-fold for Fe, eight- to 10-fold for Al and Mn and up to four-fold for Cr, Ni, Co, Pb and REEs by GMW. However, the contribution of GMW to inorganic nutrients and DOC was negligible. The significance of GMW-borne REE contribution in this cove was further evidenced by middle REE enrichment in cove water. Our results suggest that the currently increasing glacier melting in Antarctica has a significant influence on the level of trace elements, particularly Fe, in cove water, which in turn may have a significant impact on the biogeochemistry of coastal seawater in Antarctica. Keywords: Iron; trace elements; rare earth elements; glacier melting; Antarctica; Marian Cove.
Keywords: Antarktis; biogeokjemi; isbreer; kjemiske analyser; sjøvann; smelting

Methane and nitrous oxide fluxes in relation to vegetation covers and bird activity in ice-free soils of Rip Point, Nelson Island, Antarctica - Neufeld, Ângela Denise Hubert; de Godoi, Stefânia Guedes; Pereira, Antônio Batista; Bayer, Cimélio; Schünemann, Andriano Luis; de Carvalho Victoria, Filipe; de Albuquerque, Margéli Pereira; Camargo, Estefânia; Vieira, Frederico Costa Beber (Polar Research, 2015)
This study aimed to quantify the nitrous oxide (N2O) and methane (CH4) fluxes at sites with different vegetation covers and where bird activity was present or absent using the static chamber method, on Rip Point, Nelson Island, maritime Antarctic. The sites were soils covered by Sanionia uncinata, lichens, Prasiola crispa, Deschampsia antarctica and bare soil. Seabirds used the P. crispa and D. antarctica sites as nesting areas. Soil mineral N contents, air and soil temperature and water-filled pore space were measured, and the content of total organic C and particulate organic C, total N, bulk density and texture were determined to identify controlling variables of the gas emissions. The N2O and CH4 flux rates were low for all sampling events. Mean N2O flux rates ranged from 0.11±1.93 up to 21.25±22.14 µg N2O m−2 h−1 for the soils under lichen and P. crispa cover, respectively. For the CH4 fluxes, only the P. crispa site showed a low positive mean (0.47±3.61 µg CH4 m−2 h−1). The bare soil showed the greatest absorption of CH4 (−11.92±5.7 µg CH4 m−2 h−1), probably favoured by the coarse soil texture. Bare soil and S. uncinata sites had N2O accumulated emissions close to zero. Net CH4 accumulated emission was observed only at the P. crispa site, which was correlated with (p<0.001). These results indicate that seabird activity influences N2O and CH4 soil fluxes, while vegetation has little influence, and bare soil areas in maritime Antarctica could be greenhouse gas sinks. Keywords: Soil greenhouse gases; seabirds; vegetal cover; maritime Antarctica.
Keywords: Antarktis; biogeokjemi; drivhuseffekt; drivhusgasser; flora; global oppvarming; klimaendringer; klimagasser; planter; sjøfugler; økosystemer

Atmospheric trace elements in aerosols observed over the Southern Ocean and coastal East Antarctica - Xu, Guojie; Gao, Yuan (Polar Research, 2014)
Atmospheric aerosol samples were collected over the Southern Ocean (SO) and coastal East Antarctica (CEA) during the austral summer of 2010/11. Samples were analysed for trace elements, including Na, Mg, K, Al, Fe, Mn, Ni, Cd and Se, by inductively coupled plasma mass spectrometry (ICP-MS). The mean atmospheric concentrations over the SO were 1100 ng m−3 for Na, 190 ng m−3 for Mg, 150 ng m−3 for Al, 14 ng m−3 for Fe, 0.46 ng m−3 for Mn and 0.25 ng m−3 for Se. Over CEA, the mean concentrations were 990 ng m−3 for Na, 180 ng m−3 for Mg, 190 ng m−3 for Al, 26 ng m−3 for Fe, 0.70 ng m−3 for Mn and 0.29 ng m−3 for Se. Particle size distributions, enrichment factors (EFs) and correlation analysis indicate that Na, Mg and K mainly came from the marine source, while Al, Fe and Mn were mainly from the crustal source, which also contributed to Mg and K over CEA. High EFs were associated with Ni, Cd and Se, suggesting likely contributions from mixed sources from the Antarctic continent, long-range transport, marine biogenic emissions and anthropogenic emissions. Sea-salt elements (Na, Mg, K) were mainly accumulated in the coarse mode, and crustal elements (Al, Fe, Mn) presented a bimodal size distribution pattern. Bioactive elements (Fe, Ni, Cd) were enriched in the fine mode, especially with samples collected over the SO, possibly affecting biogeochemical cycles in this oceanic region. Keywords: Southern Ocean; coastal East Antarctica; trace elements; size distribution; sources.
Keywords: Sørishavet; atmosfærisk aerosol; biogeokjemi; kjemiske analyser; meteorologi

Using visible reflectance spectroscopy to reconstruct historical changes in chlorophyll a concentration in East Antarctic ponds - Chen, Qianqian; Liu, Xiaodong; Nie, Yaguang; Sun, Liguang (Polar Research, 2013)
The visible reflectance spectroscopy (VRS) and chlorophyll a concentration were determined in three sediment profiles collected from East Antarctica to investigate the potential application of VRS in reconstructing historical changes in Antarctic lake primary productivity. The results showed that the appearance of a trough at 650–700 nm is an important marker for chlorophyll a concentration and can therefore be used to distinguish the sedimentary organic matter source from guano and algae. The measured chlorophyll a content had significant positive correlations with the trough area between 650 and 700 nm, and no distinct trough was found in the sediments with organic matter completely derived from guano. Modelling results showed that the spectra spectrally inferred chlorophyll a content, and the measured data exhibit consistent trends with depth, showing that the dimensionless trough area can serve as an independent proxy for reconstructing historical fluctuations in the primary production of Antarctic ponds. The correlation of phosphorus (P) with measured and inferred chlorophyll a contents in ornithogenic sediments near penguin colonies indicates that the change in primary productivity in the Antarctic ponds investigated was closely related to the amount of guano input from these birds. Keywords: Reflectance spectroscopy; ornithogenic sediments; chlorophyll a; Antarctic ponds; primary productivity; VRS.
Keywords: Antarktis; alger; biogeokjemi; fytoplankton; innsjø; pingviner; sedimenter; sjøfugler

Assessing the potential of calcium-based artificial ocean alkalinization to mitigate rising atmospheric CO2 and ocean acidification - Ilyina, Tatiana; Wolf-Gladrow, Dieter; Munhoven, Guy; Heinze, Christoph (Geophysical Research Letters, 2013)
Enhancement of ocean alkalinity using calcium compounds, e.g., lime has been proposed to mitigate further increase of atmospheric CO2 and ocean acidification due to anthropogenic CO2 emissions. Using a global model, we show that such alkalinization has the potential to preserve pH and the saturation state of carbonate minerals at close to today's values. Effects of alkalinization persist after termination: Atmospheric CO2 and pH do not return to unmitigated levels. Only scenarios in which large amounts of alkalinity (i.e., in a ratio of 2:1 with respect to emitted CO2) are added over large ocean areas can boost oceanic CO2 uptake sufficiently to avoid further ocean acidification on the global scale, thereby elevating some key biogeochemical parameters, e.g., pH significantly above preindustrial levels. Smaller-scale alkalinization could counteract ocean acidification on a subregional or even local scale, e.g., in upwelling systems. The decrease of atmospheric CO2 would then be a small side effect.
Keywords: Sørishavet; biogeokjemi; havalkalisering; klimatologi; meteorologi; modeller

Implications of meltwater pulse events for soil biology and biogeochemical cycling in a polar desert - Ball, Becky A; Barrett, J E; Gooseff, Mike N; Virginia, Ross A; Wall, Diana H (Polar Research, 2011)
The McMurdo Dry Valleys are one of the most arid environments on Earth. Over the soil landscape for the majority of the year, biological and ecosystem processes in the dry valleys are constrained by the low temperatures and limited availability of water. The prevalence of these physical limitations in controlling biological and ecosystem processes makes the dry valleys a climatesensitive system, poised to experience substantial changes following projected future warming. Short-duration increases in summer temperatures are associated with pulses of water from melting ice reserves, including glaciers, snow and permafrost. Such pulses alter soil geochemistry by mobilizing and redistributing soil salts (via enhanced weathering, solubility and mobility), which can alter habitat suitability for soil organisms. Resulting changes in soil community composition or distribution may alter the biogeochemical processes in which they take part. Here, we review the potential impacts of meltwater pulses and present new field data documenting instances of meltwater pulse events that result from different water sources and hydrological patterns, and discuss their potential influence on soil biology and biogeochemistry. We use these examples to discuss the potential impacts of future climate change on the McMurdo Dry Valley soil ecosystem.Keywords: Water pulse; climate change; polar desert; International Polar Year; discrete warming events; soil biogeochemistry.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); IPY; biogeokjemi; biologi; jord; klimaendringer; polarørken

Some like it cold: microbial transformations of mercury in polar regions - Barkay, Tamar; Kroer, Niels; Poulain, Alexandre J (Polar Research, 2011)
The contamination of polar regions with mercury that is transported from lower latitudes as inorganic mercury has resulted in the accumulation of methylmercury (MeHg) in food chains, risking the health of humans and wildlife. While production of MeHg has been documented in polar marine and terrestrial environments, little is known about the responsible transformations and transport pathways and the processes that control them. We posit that as in temperate environments, microbial transformations play a key role in mercury geochemical cycling in polar regions by: (1) methylating mercury by one of four proposed pathways, some not previously described; (2) degrading MeHg by activities of mercury resistant and other bacteria; and (3) carrying out redox transformations that control the supply of the mercuric ion, the substrate of methylation reactions. Recent analyses have identified a high potential for mercury-resistant microbes that express the enzyme mercuric reductase to affect the production of gaseous elemental mercury when and where daylight is limited. The integration of microbially mediated processes in the paradigms that describe mercury geochemical cycling is therefore of high priority especially in light of concerns regarding the effect of global warming and permafrost thawing on input of MeHg to polar regions. Keywords: Microbiology; mercury biogeochemistry; redox transformations; polar regions; methylation
Keywords: Antarktis; biogeokjemi; forurensning; mikrobiologi; miljøvern; polarområdene; økosystemer

Spring phytoplankton onset after the ice break-up and sea-ice signature (Adélie Land, East Antarctica) - Riaux-Gobin, Catherine; Poulin, Michel; Dieckmann, Gerhard; Labrune, Céline; Vétion, Gilles (Polar Research, 2011)
The phytoplankton onset following the spring ice break-up in Adélie Land, East Antarctica, was studied along a short transect, from 400 m off the continent to 5 km offshore, during the austral summer of 2002. Eight days after the ice break-up, some large colonial and solitary diatom cells, known to be associated with land-fast ice and present in downward fluxes, were unable to adapt in ice-free waters, while some other solitary and short-colony forming taxa (e.g., Fragilariopsis curta, F. cylindrus) did develop. Pelagic species were becoming more abundant offshore, replacing the typical sympagic (ice-associated) taxa. Archaeomonad cysts, usually associated with sea ice, were recorded in the surface waters nearshore. Rough weather restricted the data set, but we were able to confirm that some microalgae may be reliable sea-ice indicators and that seeding by sea ice only concerns a few taxa in this coastal area of East Antarctica. Keywords: Ice break-up; phytoplankton; sea-ice signature; East Antarctica
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; havis; oseanografi; sjøis

Natural iron enrichment around the Antarctic Peninsula in the Southern Ocean - Ardelan, M. V.; Holm-Hansen, O.; Hewes, C. D.; Reiss, C. S.; Silva, N. S.; Dulaiova, H.; Steinnes, E.; Sakshaug, E. (Biogeosciences, 2010)
As part of the US-AMLR program in January-February of 2006, 99 stations in the South Shetland Islands-Antarctic Peninsula region were sampled to understand the variability in hydrographic and biological properties related to the abundance and distribution of krill in this area. Concentrations of dissolved iron (DFe) and total acid-leachable iron (TaLFe) were measured in the upper 150 m at 16 of these stations (both coastal and pelagic waters) to better resolve the factors limiting primary production in this area and in downstream waters of the Scotia Sea. The concentrations of DFe and TaLFe in the upper mixed layer (UML) were relatively high in Weddell Sea Shelf Waters (~0.6 nM and 15 nM, respectively) and low in Drake Passage waters (~0.2 nM and 0.9 nM, respectively). In the Bransfield Strait, representing a mixture of waters from the Weddell Sea and the Antarctic Circumpolar Current (ACC), concentrations of DFe were ~0.4 nM and of TaLFe ~1.7 nM. The highest concentrations of DFe and TaLFe in the UML were found at shallow coastal stations close to Livingston Island (~1.6 nM and 100 nM, respectively). The ratio of TaLFe:DFe varied with the distance to land: ~45 at the shallow coastal stations, ~15 in the high-salinity waters of Bransfield Strait, and ~4 in ACC waters. Concentrations of DFe increased slightly with depth in the water column, while that of TaLFe did not show any consistent trend with depth. Our Fe data are discussed in regard to the hydrography and water circulation patterns in the study area, and with the hypothesis that the relatively high rates of primary production in the central regions of the Scotia Sea are partially sustained by natural iron enrichment resulting from a northeasterly flow of iron-rich coastal waters originating in the South Shetland Islands-Antarctic Peninsula region.
Keywords: Sør-Shetlandsøyene; Sørishavet; biogeokjemi; fytoplankton; hydrografi; marin biologi; marin kjemi; oseanografi

An isopycnic ocean carbon cycle model - Assmann, K. M.; Bentsen, M.; Segschneider, J.; Heinze, C. (Geoscientific Model Development, 2010)
The carbon cycle is a major forcing component in the global climate system. Modelling studies, aiming to explain recent and past climatic changes and to project future ones, increasingly include the interaction between the physical and biogeochemical systems. Their ocean components are generally z-coordinate models that are conceptually easy to use but that employ a vertical coordinate that is alien to the real ocean structure. Here, we present first results from a newly-developed isopycnic carbon cycle model and demonstrate the viability of using an isopycnic physical component for this purpose. As expected, the model represents well the interior ocean transport of biogeochemical tracers and produces realistic tracer distributions. Difficulties in employing a purely isopycnic coordinate lie mainly in the treatment of the surface boundary layer which is often represented by a bulk mixed layer. The most significant adjustments of the ocean biogeochemistry model HAMOCC, for use with an isopycnic coordinate, were in the representation of upper ocean biological production. We present a series of sensitivity studies exploring the effect of changes in biogeochemical and physical processes on export production and nutrient distribution. Apart from giving us pointers for further model development, they highlight the importance of preformed nutrient distributions in the Southern Ocean for global nutrient distributions. The sensitivity studies show that iron limitation for biological particle production, the treatment of light penetration for biological production, and the role of diapycnal mixing result in significant changes of nutrient distributions and liniting factors of biological production.
Keywords: Sørishavet; biogeokjemi; karbon syklus; klimamodeller

Biogeochemical weathering under ice: Size matters - Wadham, Jemma L; Tranter, Martyn; Skidmore, Mark; Hodson, Andy; Priscu, John C; Lyons, W Berry; Sharp, Martin; Wynn, Peter; Jackson, Miriam (Global Biogeochemical Cycles, 2010)
The basal regions of continental ice sheets are gaps in our current understanding of the Earth's biosphere and biogeochemical cycles. We draw on existing and new chemical data sets for subglacial meltwaters to provide the first comprehensive assessment of sub-ice sheet biogeochemical weathering. We show that size of the ice mass is a critical control on the balance of chemical weathering processes and that microbial activity is ubiquitous in driving dissolution. Carbonate dissolution fueled by sulfide oxidation and microbial CO2 dominate beneath small valley glaciers. Prolonged meltwater residence times and greater isolation characteristic of ice sheets lead to the development of anoxia and enhanced silicate dissolution due to calcite saturation. We show that sub-ice sheet environments are highly geochemically reactive and should be considered in regional and global solute budgets. For example, calculated solute fluxes from Antarctica (72–130 t yr−1) are the same order of magnitude as those from some of the world's largest rivers and rates of chemical weathering (10–17 t km−2 yr−1) are high for the annual specific discharge (2.3–4.1 × 10−3 m). Our model of chemical weathering dynamics provides important information on subglacial biodiversity and global biogeochemical cycles and may be used to design strategies for the first sampling of Antarctic Subglacial Lakes and other sub-ice sheet environments for the next decade.
Keywords: Antarktis; biogeokjemi; biosfære; brehylle; glasiologi; innlandsis; isbrem; isshelf; subglasial biodiversitet; subglasial innsjø

Shelf-derived iron inputs drive biological productivity in the southern Drake Passage - Dulaiova, H.; Ardelan, M. V.; Henderson, P. B.; Charette, M. A. (Global Biogeochemical Cycles, 2009)
In the Southern Ocean near the Antarctic Peninsula, Antarctic Circumpolar Current (ACC) fronts interact with shelf waters facilitating lateral transport of shelf-derived components such as iron into high-nutrient offshore regions. To trace these shelf-derived components and estimate lateral mixing rates of shelf water, we used naturally occurring radium isotopes. Short-lived radium isotopes were used to quantify the rates of shelf water entrainment while Fe/228Ra ratios were used to calculate the Fe flux. In the summer of 2006 we found rapid mixing and significant lateral iron export, namely, a dissolved iron flux of 1.1 × 105 mol d−1 and total acid leachable iron flux of 1.1 × 106 mol d−1 all of which is transported in the mixed layer from the shelf region offshore. This dissolved iron flux is significant, especially considering that the bloom observed in the offshore region (0.5–2 mg chl a m−3) had an iron demand of 1.1 to 4 × 105 mol Fe. Net vertical export fluxes of particulate Fe derived from 234Th/238U disequilibrium and Fe/234Th ratios accounted for only about 25% of the dissolved iron flux. On the other hand, vertical upward mixing of iron rich deeper waters provided only 7% of the lateral dissolved iron flux. We found that similarly to other studies in iron-fertilized regions of the Southern Ocean, lateral fluxes overwhelm vertical inputs and vertical export from the water column and support significant phytoplankton blooms in the offshore regions of the Drake Passage.
Keywords: Sørishavet; Sørishavsstrømmen; biogeokjemi; fytoplankton; marin kjemi; oseanografi; radiumisotoper

Regeneration of Fe(II) during EIFeX and SOFeX - Croot, Peter L.; Bluhm, Kathrin; Schlosser, Christian; Streu, Peter; Breitbarth, Eike; Frew, Russell D.; Ardelan, Murat van (Geophysical Research Letters, 2008)
Investigations into Fe(II) cycling during two Southern Ocean mesoscale iron enrichment experiments, SOFeX and EIFeX, clearly show the importance of Fe(II) to iron speciation during these experiments. In both cases the added Fe(II) persisted significantly longer than its expected oxidation time indicating a significant Fe reduction process at work. During EIFeX diel studies showed a strong photochemically induced cycle in Fe(II) production in sunlit surface waters. Our results suggest that the photochemical cycling of iron may also be important in unfertilized waters of the Southern Ocean.
Keywords: Sørishavet; biogeokjemi; fytoplankton; marin biologi; polarområdene

Iron and mixing affect biological carbon uptake in SOIREE and EisenEx, two Southern Ocean iron fertilisation experiments - Bakker, Dorothee C.E.; Bozec, Yann; Nightingale, Philip D.; Goldson, Laura; Messias, Marie-José; de Baar, Hein J.W.; Liddicoat, Malcolm; Skjelvan, Ingunn; Strass, Volker; Watson, Andrew J. (Deep Sea Research Part I: Oceanographic Research Papers, 2005)
This study explores the changes in the surface water fugacity of carbon dioxide (fCO2) and biological carbon uptake in two Southern Ocean iron fertilisation experiments with different hydrographic regimes. The Southern Ocean Iron Release Experiment (SOIREE) experiment was carried out south of the Antarctic Polar Front (APF) at 61°S, 141°E in February 1999 in a stable hydrographic setting. The EisenEx experiment was conducted in a cyclonic eddy north of the APF at 48°S, 21°E in November 2000 and was characterised by a rapid succession of low to storm-force wind speeds and dynamic hydrographic conditions. The iron additions promoted algal blooms in both studies. They alleviated algal iron limitation during the 13-day SOIREE experiment and probably during the first 12 days of EisenEx. The fCO2 in surface water decreased at a constant rate of 3.8μatmday−1 from 4 to 5 days onwards in SOIREE. The fCO2 reduction was 35μatm after 13 days. The evolution of surface water fCO2 in the iron-enriched waters (or ‘patch’) displayed a saw tooth pattern in EisenEx, in response to algal carbon uptake in calm conditions and deep mixing and horizontal dispersion during storms. The maximum fCO2 reduction was 18–20μatm after 12 and 21 days with lower values in between. The iron-enriched waters in EisenEx absorbed four times more atmospheric CO2 than in SOIREE between 5 and 12 days, as a result of stronger winds. The total biological uptake of inorganic carbon across the patch was 1389ton C (±10%) in SOIREE and 1433ton C (±27%) in EisenEx after 12 days (1ton=106g). This similarity probably reflects the comparable size of the iron additions, as well as algal growth at a similar near-maximum growth rate in these regions. The findings imply that the different mixing regimes had less effect on the overall biological carbon uptake across the iron-enriched waters than suggested by the evolution of fCO2 in surface water.
Keywords: Sørishavet; alger; biogeokjemi; hydrografi; karbondioksid; marin kjemi; oseanografi

The distribution and speciation of iron along 6°E in the Southern Ocean - Croot, Peter L.; Andersson, Karen; Öztürk, Murat; Turner, David R. (The SWEDARP 1997/98 Expedition, 2004)
The distribution and speciation of iron was determined along a transect in the eastern Atlantic sector (6°E) of the Southern Ocean during a collaborative Scandinavian/South African Antarctic cruise conducted in late austral summer (December 1997/January 1998). Elevated concentrations of dissolved iron (>0.4nM) were found at 60°S in the vicinity of the Spring Ice Edge (SIE) in tandem with a phytoplankton bloom, chiefly dominated by Phaeocystis sp. This bloom had developed rapidly after the loss of the seasonal sea ice cover. The iron that fuelled this bloom was mostly likely derived from sea ice melt. In the Winter Ice Edge (WIE), around 55°S, dissolved iron concentrations were low (<0.2nM) and corresponded to lower biological productivity, biomass. In the Antarctic Polar Front, at approximately 50°S, a vertical profile of dissolved iron showed low concentrations (<0.2nM); however, a surface survey showed higher concentrations (1–3nM), and considerable patchiness in this dynamic frontal region. The chemical speciation of iron was dominated by organic complexation throughout the study region. Organic iron-complexing ligands ([L]) ranged from 0.9 to 3.0nM Fe equivalents, with complex stability logKFeL′=21.4–23.5. Estimated concentrations of inorganic iron (Fe′) ranged from 0.03 to 0.79pM, with the highest values found in the Phaeocystis bloom in the SIE. A vertical profile of iron-complexing ligands in the WIE showed a maximum consistent with a biological source for ligand production and near surface minimum possibly consistent with loss via photodecomposition. This work further confirms the role iron that has in the Southern Ocean in limiting primary productivity.
Keywords: Bouvetøya; Sørishavet; biogeokjemi; marin kjemi; oseanografi

Evaluating global ocean carbon models: The importance of realistic physics - Doney, Scott C; Lindsay, Keith; Caldeira, Ken; Campin, J.-M.; Drange, Helge; Dutay, Jean-Claude; Follows, Michael; Gao, Yongqi; Gnanadesikan, Anand; Gruber, N; Ishida, Akio; Joos, Fortunat; et al. (Global Biogeochemical Cycles, 2004)
A suite of standard ocean hydrographic and circulation metrics are applied to the equilibrium physical solutions from 13 global carbon models participating in phase 2 of the Ocean Carbon-cycle Model Intercomparison Project (OCMIP-2). Model-data comparisons are presented for sea surface temperature and salinity, seasonal mixed layer depth, meridional heat and freshwater transport, 3-D hydrographic fields, and meridional overturning. Considerable variation exists among the OCMIP-2 simulations, with some of the solutions falling noticeably outside available observational constraints. For some cases, model-model and model-data differences can be related to variations in surface forcing, subgrid-scale parameterizations, and model architecture. These errors in the physical metrics point to significant problems in the underlying model representations of ocean transport and dynamics, problems that directly affect the OCMIP predicted ocean tracer and carbon cycle variables (e.g., air-sea CO2 flux, chlorofluorocarbon and anthropogenic CO2 uptake, and export production). A substantial fraction of the large model-model ranges in OCMIP-2 biogeochemical fields (±25–40%) represents the propagation of known errors in model physics. Therefore the model-model spread likely overstates the uncertainty in our current understanding of the ocean carbon system, particularly for transport-dominated fields such as the historical uptake of anthropogenic CO2. A full error assessment, however, would need to account for additional sources of uncertainty such as more complex biological-chemical-physical interactions, biases arising from poorly resolved or neglected physical processes, and climate change.
Keywords: Sørishavet; biogeokjemi; hydrografi; karbon syklus; karbondioksid; klimaendringer; oseanografi

Renewal time and transport of unventilated Central Intermediate Water of the Weddell Sea derived from biogeochemical properties - Hoppema, Mario; de Baar, Hein J. W.; Fahrbach, Eberhard; Bellerby, Richard G. J. (Journal of Marine Research, 2002)
We have investigated the intermediate water mass of the central Weddell Gyre using TCO2 and oxygen data of FS Polarstern cruises in 1992, 1996 and 1998. This water mass, designated as Central Intermediate Water (CIW), is enriched in CO2 and depleted in O-2 relative to its source water due to biological degradation. CO2 enrichment and O-2 depletion were quantified by calculating the difference between the concentrations in the CIW and those in the, more southern source water, the Circumpolar Deep Water, which derives from the Antarctic Circumpolar Current. Inventories of enrichment and depletion were determined over the whole depth range of CIW, i.e. about 200800 m. The O-2 depletion inventory was greater than that of TCO2 enrichment which is in line with a biological origin of the signal. Spatial and interannual variation appeared to be small. Because subsurface remineralization in the central Weddell Gyre is largely restricted to the CIW, the export production estimate from previous work has been applied to compute the renewal time of CIW from these inventories. A renewal time of only three years was found. TCO2- and O-2-based computations were consistent, the former showing larger variation, though. From renewal time and volume of the CIW, a transport velocity (renewal rate) of 6-7 Sv was obtained. Of this, about I Sv is upwelled into the surface layer. The remaining 5-6 Sv CIW must be exported to the north, which is opposite to previous views. Results of water mass age and transport rate have thus been obtained using a method based on biogeochemical parameters. As the CIW cannot be identified by temperature and salinity, nor with transient tracers because it is hardly ventilated, this is the only way to obtain such results. As part of the CIW export, a large amount of remineralized CO2 enters the abyssal oceans where it is sequestered for long periods of time. The CIW is a principal and highly efficient player in the biological pump mechanism of the Southern Ocean.
Keywords: AABW; Sørishavet; Weddellhavet; biogeokjemi; geofysikk; havstrømmer; oseanografi; vannmasser

Ecology of sea ice biota. 2. Global significance - Legendre, Louis; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjørn; Horner, Rita; Hoshiai, Takao; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
The sea ice does not only determine the ecology of ice biota, but it also influences the pelagic systems under the ice cover and at ice edges. In this paper, new estimates of Arctic and Antarctic production of biogenic carbon are derived, and differences as well as similarities between the two oceans are examined. In ice-covered seas, high algal concentrations (blooms) occur in association with several types of conditions. Blooms often lead to high sedimentation of intact cells and faecal pellets. In addition to ice-related blooms, there is progressive accumulation of organic matter in Arctic multi-year ice, whose fate may potentially be similar to that of blooms. A fraction of the carbon fixed by microalgae that grow in sea ice or in relation to it is exported out of the production zone. This includes particulate material sinking out of the euphotic zone, and also material passed on to the food web. Pathways through which ice algal production does reach various components of the pelagic and benthic food webs, and through them such top predators as marine mammals and birds, are discussed. Concerning global climate change and biogeochemical fluxes of carbon, not all export pathways from the euphotic zone result in the sequestration of carbon for periods of hundreds of years or more. This is because various processes, that take place in both the ice and the water column, contribute to mineralize organic carbon into CO2 before it becomes sequestered. Processes that favour the production and accumulation of biogenic carbon as well as its export to deep waters and sequestration are discussed, together with those that influence mineralization in the upper ice-covered ocean.
Keywords: Sørishavet; biodiversitet; biogeokjemi; havis; karbondioksid; klimaendringer; marin biologi; polarområdene; økologi